Extraction and partial purification for adhesive protein FimH from type-1 pili which isolated from uorpathogenic E.coli - Alice K. M; Mouruj A. alaubydi (مجلة بغداد للعلوم)
Type-1 fimbriae have been extracted from E.coli which was previously isolated, the yield was 2.8 mg fimbriae/10 g bacteria , the crude fimbriae was partially purified by several solubilization and recrystilization methods using a series of buffer and solutions to decrease the impurities, the yield of fimbriae from all these steps was 2.1 mg fimbriae / 10 g bacteria.